Effective Strategies for Interdisciplinary Integration in STEAM Curriculum Design - Li, Jiameng (Transactions on Social Science, Education and Humanities Research, 2024)
This article explores effective strategies for interdisciplinary integration in STEAM curriculum design, analyses its importance in developing students’ creativity and problem-solving skills, and proposes specific coping strategies in the face of implementation challenges. STEAM education emphasises the integration of science, technology, engineering, art, and maths, aiming to provide a richer, more hands-on learning experience through the synthesis of these disciplines. The article first discusses the theoretical underpinnings of STEAM education, including constructivist learning theory, multiple intelligence theory, and creativity theory, which underpin the effectiveness of the interdisciplinary education model. Subsequently, the article details key pedagogical models of interdisciplinary integration, such as project-based learning, thematic teaching and case studies, which are effective in linking different disciplines and facilitating deeper student learning and understanding. In addition, the article discusses the major challenges encountered in designing and implementing interdisciplinary STEAM programmes, such as teacher professional development, innovations in student assessment, resource allocation and policy support, and proposes specific strategies to address these challenges. Finally, the paper summarises best practices in interdisciplinary STEAM education and makes recommendations for future educational policies and school practices. By strengthening teachers’ interdisciplinary professional development, innovating assessment methods, optimising resource allocation and obtaining policy support, the implementation of STEAM education can be effectively promoted to provide students with a holistic and innovative learning environment. This mode of education can not only enhance students’ mastery of subject knowledge, but more importantly, develop their ability to face future challenges.